Recomposing the self: Joyful shame in Dorothy Allison's "Bastard Out of Carolina" - Walerstein, Rachel (Mosaic: An Interdisciplinary Critical Journal, 2016)
Dorothy Allison’s Bastard Out of Carolina is typically read as representative of the negative effects of trauma. This essay suggests that one’s shame can be used to recompose the shamed self, enabling one to (re)connect with others.
Keywords: approches et analyses; arts; discipline; honte; personnes lesbiennes; queer; ressource en ligne; émotions; études littéraires